Scalar bosons with Coulomb potentials in a cosmic string background: scattering and bound states - Neto, Francisco A. Cruz; da Silva, Franciele M.; Santos, Luis C. N.; Castro, Luis B. [UNESP] (Springer Nature, 2020)
The relativistic quantum motion of scalar bosons under the influence of a full vector (minimal Aμ and nonminimal Xμ) and scalar (Vs) interactions embedded in the background of a cosmic string is explored in the context of the Klein–Gordon equation. Considering Coulomb interactions, the effects of this topological defect in equation of motion, phase shift and S-matrix are analyzed and discussed. Bound-state solutions are obtained from poles of the S-matrix and it is shown that bound-state solutions are possible only for a restrict range of coupling constants.